2018
DOI: 10.1109/lmwc.2018.2808418
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Independent Analysis of the Double Current-Gain Peak in Millimeter-Wave FETs

Abstract: This letter is aimed at discovering and analyzing anomalous phenomena affecting millimeter-wave FETs, focusing on a GaN HEMT as a case study. For the first time, we show that the real parts of the impedance parameters can increase and then decrease with frequency, due to the resonance of the extrinsic reactive elements. This resonance may be detected as a peak in the magnitude of the short-circuit current-gain. Such a peak is found to be substantially bias and temperature insensitive and to manifest at frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 10 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…The physical origin of the R 3 C 3 network might be ascribed to the high-frequency skin-effect losses, deviations further away from TEM-like propagation (e.g., surface-wave modes leading to high-frequency losses and dispersion as a result of the dielectric mismatch), and limitations of the lumped-element approximation at higher frequencies. It should be highlighted that, analogously to the fact that the studied IDC sensor loaded with a MUT having high ε r exhibits a peak in Re(Z) at frequencies beyond the resonant frequency of the admittance, large (field-effect transistors) FETs based on multi-finger lay-out exhibit a peak in the real part of each impedance parameter at frequencies beyond the cutoff frequency (f T ), turning into a current-gain peak and originating from a resonance of the extrinsic reactive elements [51,52].…”
Section: Modified Version Of the Equivalent Circuitmentioning
confidence: 99%
“…The physical origin of the R 3 C 3 network might be ascribed to the high-frequency skin-effect losses, deviations further away from TEM-like propagation (e.g., surface-wave modes leading to high-frequency losses and dispersion as a result of the dielectric mismatch), and limitations of the lumped-element approximation at higher frequencies. It should be highlighted that, analogously to the fact that the studied IDC sensor loaded with a MUT having high ε r exhibits a peak in Re(Z) at frequencies beyond the resonant frequency of the admittance, large (field-effect transistors) FETs based on multi-finger lay-out exhibit a peak in the real part of each impedance parameter at frequencies beyond the cutoff frequency (f T ), turning into a current-gain peak and originating from a resonance of the extrinsic reactive elements [51,52].…”
Section: Modified Version Of the Equivalent Circuitmentioning
confidence: 99%
“…However, it is quite often noticed that at high frequencies, h 21 deviates from its optimal behavior, owing to the occurrence of the current‐gain peak (CGP). The earlier studies have demonstrated that the origin of the CGP is because of the resonance of extrinsic inductances and the intrinsic capacitances . It has been shown that such a resonance leads to a dip in the open‐circuit output impedance magnitude ( Z 22 ), thereby turning into the peak in h 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The CGP has been investigated by means of the second derivative of the magnitude of h 21 against the frequency, enabling the determination of a set of parameters to fully and systematically characterize the CGP . Over the years, the peak in h 21 has been extensively studied under a wide range of working conditions, such as different bias points, device sizes, and high temperatures . To further advance the understanding of this phenomenon, the present study investigates for the first time the peak in h 21 for not only heated but also cooled device.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations